Wogonin and its analogs for the prevention and treatment of cancer: A systematic review - Banik, Kishore; Khatoon, Elina; Harsha, Choudhary; Rana, Varsha; Parama, Dey; Thakur, Krishan Kumar; Bishayee, Anupam; Kunnumakkara, Ajaikumar B. (Phytotherapy research, 2022)
The medicinal plant Scutellaria baicalensis, commonly known as Chinese skullcap or Huang‐Qin, has been used as a traditional medicine for several thousand years. The roots of this plant contain bioactive compounds, such as wogonin (WOG), wogonoside, baicalein, and baicalin. The aim of this article is to evaluate the therapeutic potential and mechanisms of action of WOG against different cancers. Numerous in vitro and in vivo studies have revealed that WOG exerts immense therapeutic potential against bladder cancer, breast cancer, cholangiocarcinoma, cervical cancer, colorectal cancer, gallbladder cancer, gastric cancer, glioblastoma, head and neck cancer, hepatic cancer, leukemia, lung cancer, lymphoma, melanoma, multiple myeloma, neuroblastoma, osteosarcoma, ovarian cancer, pancreatic cancer, prostate cancer, and renal cancer by regulating various cell signaling pathways. WOG, in combination with established chemotherapeutic drugs, improves the efficacy of treatment and lowers toxicity. Nevertheless, human trials are warranted to validate these findings. Numerous preclinical studies, combined with an extensive margin of safety and no severe side effects, underscore WOG's therapeutic potential as an anticancer drug. These studies propound the use of WOG as a potential anticancer candidate; however, further high‐quality studies are required to firmly establish the clinical efficacy of WOG for the prevention and treatment of human malignancies.